EVALUASI KANDUNGAN VITAMIN CDALAM MADU RANDU DAN MADU KELENGKENG DARI PETERNAK LEBAH DAN MADU PERDAGANGAN DI KOTA SEMARANG - Aqnes Budiarti; Sumantri Sumantri; Diah Fahmisul Istiyaningrum (Universitas Wahid Hasyim Semarang, 2012)
ABSTRACT Key words: vitamin C, cottonwoods honey, longan honey, HPLC Honey is a natural product that containing several vitamins, including vitamin C, which has an important role to maintain health, among others helps healing wound, increase body resistance fight infection and as antioxidant. This research aimed to determine the levels of vitamin C in the cottonwoods honey and longan honey from beekeepers and honey trade in the city of Semarang using HPLC.Samples consisted of three samples of honey and three cottonwoods honey and longan honey from beekeepers different (Ambarawa, Ngaliyan, Gringsing) and honey trade in the city of Semarang. HPLC (waters ec 2695) operational conditions is equipped stationary phase C18 column (C18 5um sunfire; 4.6 X150 mm), and the mobile phase is a mixture of phosphate buffer pH 3.6 and acetonitrile with the ratio 70: 30, v / v, flow rate of 0.5 ml / min. Detection use UV detector (UV / vis water in 2489) at 260 nm wavelength.Research results show ed that the average levels of vitamin C in the cottonwoods honey from beekeepers and honey cottonwoods trade in the city of Semarang are 0,034% and 0,016%, while for longan honey respectively 0,027% and 0,032%. The average level of the twelve samples of honey contain vitamin C, but there are two samples that does not contain vitamin C. There was no significant difference between the levels of vitamin C and cottonwoods honey and longan honey from beekeepers and honey trade in the City of Semarang.